2023
DOI: 10.1371/journal.pgen.1010765
|View full text |Cite
|
Sign up to set email alerts
|

Rab8, Rab11, and Rab35 coordinate lumen and cilia formation during zebrafish left-right organizer development

Abstract: An essential process during Danio rerio’s left-right organizer (Kupffer’s Vesicle, KV) formation is the formation of a motile cilium by developing KV cells which extends into the KV lumen. Beating of motile cilia within the KV lumen directs fluid flow to establish the embryo’s left-right axis. However, the timepoint at which KV cells start to form cilia and how cilia formation is coordinated with KV lumen formation have not been examined. We identified that nascent KV cells form cilia at their centrosomes at r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
(115 reference statements)
0
3
0
Order By: Relevance
“…However, the formation of cilia during human node formation is not fully annotated. It is possible that in humans, cilia are formed before the development of the node, as is the case for zebrafish embryos ( Aljiboury et al, 2023 ). Like in humans, the zebrafish LRO (Kupffer's vesicle, KV) is the first annotated ciliated organ in the developing embryo ( Essner et al, 2005 ).…”
Section: Cilia During Embryonic Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the formation of cilia during human node formation is not fully annotated. It is possible that in humans, cilia are formed before the development of the node, as is the case for zebrafish embryos ( Aljiboury et al, 2023 ). Like in humans, the zebrafish LRO (Kupffer's vesicle, KV) is the first annotated ciliated organ in the developing embryo ( Essner et al, 2005 ).…”
Section: Cilia During Embryonic Developmentmentioning
confidence: 99%
“…Like in humans, the zebrafish LRO (Kupffer's vesicle, KV) is the first annotated ciliated organ in the developing embryo ( Essner et al, 2005 ). From our recent studies, we know that cilia are formed prior to KV lumen development ( Aljiboury et al, 2023 ). We found that ∼33% of KV precursor cells had cilia at the 90% epiboly stage, suggesting that cilia formation is a precursor to LRO formation.…”
Section: Cilia During Embryonic Developmentmentioning
confidence: 99%
See 1 more Smart Citation